Three Methods of Manufacturing Zirconium Dioxide-Based Dental Bridge Prostheses - Anvar, Rustamov Elshan; Eldar, Karimova Arzu; Vagif, Zeynalova Nargiz (American Journal of Biology and Natural Sciences, 2025)
This article reviews three contemporary methods for manufacturing zirconium dioxide–based dental bridge prostheses and evaluates their clinical suitability within modern prosthetic dentistry. Zirconia has become a widely used material due to its superior mechanical strength, biocompatibility, and aesthetic properties, making it a reliable alternative to metal-containing restorations. However, traditional veneered zirconia bridges frequently face clinical challenges, particularly ceramic chipping resulting from thermal mismatch, weak bonding interfaces, or structural inconsistencies. To address these limitations, two alternative methods—monolithic (full-contour) zirconia bridges and combined ceramo-ceramic bridges—have been developed. Monolithic zirconia eliminates veneer-related failures, whereas combined systems, such as Rapid Layering Technology (RLT) and CAD-On, utilize prefabricated ceramic veneers bonded through “cold” or “hot” fusion techniques to improve structural consistency and aesthetics. Each method presents specific requirements in terms of material thickness, connector design, milling limitations, and clinical indications. The article further analyzes the advantages, limitations, and technical considerations involved in fabrication, including sintering behavior, veneer bonding protocols, block size constraints, and long-term performance factors such as low-temperature degradation. Findings indicate that method selection should be guided by clinical parameters such as interocclusal space and vitality of abutment teeth. Overall, all three fabrication approaches demonstrate strong potential for reliable, predictable, and aesthetically pleasing prosthetic outcomes while minimizing human-factor variability. Continued long-term clinical evaluation is recommended to further validate their durability and performance.